Women and Their Pattern of Use of Novel Psychoactive Substances - Win Thet; Owen Bowden-Jones (BJPsych Open, 2025)
Aims: This study aims to explore the patterns of psychoactive substance use among women attending the Club Drugs Clinic. It also explores associations with demographic factors and mental health comorbidities to identify additional therapeutic needs beyond current clinical treatments. The findings will help contribute to improving service provision for this population.